Relationship between PPARα mRNA expression and mitochondrial respiratory function and ultrastructure of the skeletal muscle of patients with COPD. Issue 6 (2nd November 2017) - Zhang, Jian-Qing; Long, Xiang-Yu; Xie, Yu; Zhao, Zhi-Huan; Fang, Li-Zhou; Liu, Ling; Fu, Wei-Ping; Shu, Jing-Kui; Wu, Jiang-Hai; Dai, Lu-Ming
ABSTRACT: Peripheral muscle dysfunction is an important complication in patients with chronic obstructive pulmonary disease (COPD). The objective of this study was to explore the relationship between the levels of peroxisome proliferator-activated receptor α (PPARα) mRNA expression and the respiratory function and ultrastructure of mitochondria in the vastus lateralis of patients with COPD. Vastus lateralis biopsies were performed on 14 patients with COPD and 6 control subjects with normal lung function. PPARα mRNA levels in the muscle tissue were detected by real-time PCR. A Clark oxygen electrode was used to assess mitochondrial respiratory function. Mitochondrial number, fractional area in skeletal muscle cross-sections, and Z-line width were observed via transmission electron microscopy. The PPARα mRNA expression was significantly lower in COPD patients with low body mass index (BMIL) than in both COPD patients with normal body mass index (BMIN) and controls. Mitochondrial respiratory function (assessed by respiratory control ratio) was impaired in COPD patients, particularly in BMIL. Compared with that in the control group, mitochondrial number and fractional area were lower in the BMIL group, but were maintained in the BMIN group. Further, the Z-line became narrow in the BMIL group. PPARα mRNA expression was positively related to mitochondrial respiratory function and volume density. In COPD patients with BMIN, mitochondria volume density was maintained, while respiratory function decreased, whereas both volume density and respiratory function decreased in COPD patients with BMIL. PPARα mRNA expression levels are associated with decreased mitochondrial respiratory function and volume density, which may contribute to muscle dysfunction in COPD patients.